Tessellation planning: relationships between the physical environment and the neighbourhood / Anniz Fazli Ibrahim Bajunid, Mohamed Yusoff Abbas and Abdul Hadi Nawawi. - Ibrahim Bajunid, Anniz Fazli; Abbas, Mohamed Yusoff; Nawawi, Abdul Hadi (Universiti Teknologi MARA Cawangan Selangor, 2017)
The fundamental objective of the national housing agenda is to ensure a better quality of life. The challenge is to develop affordable houses whilst sustaining positive social neighbourhoods. In the western world, research equated the physical environment as a dominant influence on the spatial behaviours of communities. Quality of living in Malaysia is only obtainable to the upper echelons in organic planning of housing. These perceived as successful neighbourhoods such as the cul-de-sac or Tessellation Planning create a relationship between the physical environment and the neighbourhood. This paper initiates a search for such literature and identifies key concepts for further deliberations.